Targeting CD38 for acute leukemia - Zhong, Xushu; Ma, Hongbing (Frontiers in Oncology, 2022)
Acute leukemia (AL) is a hematological malignancy, and the prognosis of most AL patients hasn't improved significantly, particularly for relapsed or refractory (R/R) AL. Therefore, new treatments for R/R adult acute myeloid leukemia (AML) and acute lymphoblastic leukemia (ALL) are urgently necessary. Novel developments have been made in AL treatment, including target and immune therapies. CD38 is one of the targets due to its high expression in many hematological malignancies, including multiple myeloma, ALL and a subset of AML. Consequently, targeting CD38 therapies, including CD38 monoclonal antibodies (mAbs), bispecific antibodies, and CAR-T cell therapy, exhibit promising efficacy in treating multiple myeloma without significant toxicity and are being explored in other hematological malignancies and nonhematological diseases. Herein, this review focuses on targeting CD38 therapies in ALL and AML, which demonstrate sound antileukemic effects in acute leukemia and are expected to become effective treatment methods.